Exploring The Literary Landscape: An Annotated Bibliography On Effective Strategies For Teaching English Literature - Nani Muliyani (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The aim of this research is to explore the literary landscape: An Annotated Bibliography of Effective Strategies for Teaching English Literature. The research will primarily rely on academic databases such as JSTOR, ERIC, and Google Scholar to gather relevant scholarly articles. These databases offer extensive repositories of peer-reviewed literature, ensuring the reliability and credibility of the sources retrieved. Keywords such as “literature in higher education”, “literature pedagogy”, and “literature in English classroom” will be utilized to conduct systematic searches and identify pertinent studies.In selecting literature for inclusion in the annotated bibliography, specific criteria will be applied. Only studies publish within the last decade will be considered to ensure relevance and currency. Preference will be given to peer-reviewed articles or journals, as these sources undergo rigorous scrutiny and contribute to the scholarly discourses on the subject matter. Moreover, studies focusing solely on primary education will be excluded to maintain the focus on secondary or higher education English classrooms. The result of exploration of English Literature in Higher Education as a topic in literature education is not novel; rather, it undergoes dynamic changes over time, adapting to diverse situations and cultural contexts. Despite the existence of various topics concerning English Teaching in Higher Education, the significance of incorporating English Literature in classrooms remains steadfast. Consequently, recent articles delve into conducted studies employing relevant theories for Teaching English Literature in higher education.